Morphology of the early larval stages of Lysmata lipkei Okuno & Fiedler, 2010 (Caridea: Lysmatidae): an invasive shrimp in the Western Atlantic - Almeida, Andréa Santos E; Alves, Douglas Fernandes Rodrigues; de Paiva Barros-Alves, Samara; Pescinelli, Régis Augusto; Santos, Rafael De Carvalho; Da Costa, Rogério Caetano (Zootaxa, 2021)
Considering the importance of establishing different approaches to the early detection of invasive species, the present study aimed to describe and illustrate the morphology of the early larval stages of the shrimp Lysmata lipkei, an invasive species in the Western Atlantic. Additionally, we did a morphological comparison and a review of the other Lysmata species from the Western Atlantic Ocean with a known larvae description. The larvae used in this study were obtained by the maintenance, under laboratory conditions, of ovigerous hermaphrodites of L. lipkei, collected in the wild. Then, larvae were dissected under a stereo microscope and illustrated using a microscope equipped with a camera lucida. The first three larval stages (zoeae) of L. lipkei were illustrated, described, and compared to other species of Lysmata previously described of the Western Atlantic. Some features of the larval morphology of L. lipkei are very similar when compared to other Lysmata species with previous larval descriptions, such as a rostrum long and simple, the eyes stalked with a long peduncle from the second zoeae, one pterygostomian spine and several denticles along the anterior ventral margin of the carapace, similarities in the segmentation of the maxillipeds, and the presence of dorsolateral spines on the posterior margin of the 5th pleomere, among other features. Also, unique features were observed for L. lipkei, such as differences in the setation of some structures, including the antennule, antenna, maxillule, and maxillipeds. Using the morphological descriptions, we expect to identify species from the plankton, especially invaders, that might be present in the Western Atlantic, as well as assist in several areas in which the larval morphology is relevant.